Hemotropic mycoplasmas infection in water buffaloes (Bubalus bubalis) from northeastern Brazil. (February 2018) - Santos, Nelson J.R.; Brito, Danilo R.B.; Abate, Hugo L.; Paixão, Sonália F.; Soares, Eduardo D.S.; Vieira, Thállitha S.W.J.; Garcia, João L.; Vieira, Rafael F.C.; Vidotto, Odilon
Highlights: A high prevalence of hemoplasmas was found in water buffaloes from northeastern Brazil. This is the first report of M. wenyonii infection in ruminants from Brazil. From the total of Mycoplasma -infected buffaloes, 94.2% were by M. wenyonii . Clinical signs of hemoplasmosis in buffaloes remain unknown. Abstract: Two species of hemotropic mycoplasmas (HM) are known to infect large domestic ruminants, Mycoplasma wenyonii and ' Candidatus Mycoplasma haemobos'. Although HM has been described in cattle worldwide, data in water buffaloes ( Bubalus bubalis ) remain scarce. Accordingly, the aim was to determine the occurrence of HM in water buffaloes from northeastern Brazil. A total of 101/290 (34.83%) buffaloes were positive for HM (16 M. wenyonii alone, 6 ' Ca. M. haemobos' alone and 79 both). This was the first report of M. wenyonii infection in ruminants from Brazil. Clinical signs of hemoplasmosis in buffaloes remain unknown.